Safety and immunogenicity of the group B streptococcus vaccine AlpN in a placebo-controlled double-blind phase 1 trial - Majela Gonzalez-Miro; Andrzej Pawlowski; Janne Lehtonen; Duojia Cao; Sara Larsson; Michael Darsley; Geoff Kitson; Per B. Fischer; Bengt Johansson-Lindbom (iScience, 2023)
Summary: Group B streptococcus (GBS) is a leading cause of life-threatening neonatal infections and subsets of adverse pregnancy outcomes. Essentially all GBS strains possess one allele of the alpha-like protein (Alp) family. A maternal GBS vaccine, consisting of the fused N-terminal domains of the Alps αC and Rib (GBS-NN), was recently demonstrated to be safe and immunogenic in healthy adult women. To enhance antibody responses to all clinically relevant Alps, a second-generation vaccine has been developed (AlpN), also containing the N-terminal domain of Alp1 and the one shared by Alp2 and Alp3. In this study, the safety and immunogenicity of AlpN is assessed in a randomized, double-blind, placebo-controlled, and parallel-group phase I study, involving 60 healthy non-pregnant women. AlpN is well tolerated and elicits similarly robust and persistent antibody responses against all four Alp-N-terminal domains, resulting in enhanced opsonophagocytic killing of all Alp serotypes covered by the vaccine.